2009
DOI: 10.17221/5/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Variations in chemical compositions of Rosa damascena Mill. and Rosa canina L. fruits

Abstract: In this study, fruits, fruit flesh and seeds of damask rose (Rosa damascena Mill.) and rose hip (Rosa canina L.) were assayed for the composition of fatty acids, ascorbic acid, α-tocopherol, β-carotene, and mineral elements. The content of linoleic acid in seed oil of Rosa damascena (54.18%) was found to be higher than in that of Rosa canina (48.84%). α-Tocopherol contents were found to be 7.10 μg/g and 34.20 μg/g for Rosa damascena and Rosa canina fruits, respectively. Ascorbic acid content was determined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 23 publications
4
54
2
6
Order By: Relevance
“…The differences resulted from various extraction methods, that is, water and methanol extracts of fresh and air-dried wild rose fruits (Nadpal et al, 2016). Higher concentrations of vitamin C in the fruit of Rosa canina were reported in some other investigations: 7544.8 ± 1002 for ripe fruit (Murathan et al, 2016) and 4110 to 22000 mg/kg for fruit or flesh (Kazaz, Baydar, & Erbas, 2009). In turn, the goji juice in our study had a lower vitamin C content than acerola and wild rose juices (Table 1), but the result was much higher than reported by Ionica, Nour, and Trandafir (2012) for fresh and dried goji fruits (299 to 458 mg/kg) or showed by Potterat (2010) for goji fruits (420 mg/kg).…”
Section: Resultsmentioning
confidence: 88%
“…The differences resulted from various extraction methods, that is, water and methanol extracts of fresh and air-dried wild rose fruits (Nadpal et al, 2016). Higher concentrations of vitamin C in the fruit of Rosa canina were reported in some other investigations: 7544.8 ± 1002 for ripe fruit (Murathan et al, 2016) and 4110 to 22000 mg/kg for fruit or flesh (Kazaz, Baydar, & Erbas, 2009). In turn, the goji juice in our study had a lower vitamin C content than acerola and wild rose juices (Table 1), but the result was much higher than reported by Ionica, Nour, and Trandafir (2012) for fresh and dried goji fruits (299 to 458 mg/kg) or showed by Potterat (2010) for goji fruits (420 mg/kg).…”
Section: Resultsmentioning
confidence: 88%
“…Ascorbic wileyonlinelibrary.com/jsfa acid (vitamin C) is the most important and abundant organic acid in Rosa fruits, and several previous studies reported the ascorbic acid content for fruits of different Rosa species. [5][6][7]14,62 In the previous studies, the level of ascorbic acid varied among species, i.e. 0.56-3.…”
Section: Ascorbic Acid Contentmentioning
confidence: 94%
“…Summary of the literature data on the oil extraction yield and fatty acid profile in R. canina seed oil from raw materials from Poland, Hungary, Germany, Bulgaria, and Turkey is given in Table . In almost all cases seed oil was obtained by extraction in Soxhlet apparatus, however, different solvents were used: hexane, petroleum ether, and diethyl ether . The oil content (4.07–12.90%) varied strongly depending on the variety of the raw material but also depending on its origin .…”
Section: Oil Content and Compositionmentioning
confidence: 99%
“…FAME were usually identified by comparison of retention times with those of authentic FAME standards. In some research GC‐MS was applied as identification method . Quantitative analysis was carried out by FAME peak area relative to peak area of all FAME or to total peak area, and expressed in percentages.…”
Section: Oil Content and Compositionmentioning
confidence: 99%
See 1 more Smart Citation